Multiple Focus Strategies in Pro‐Drop Languages: Evidence from Ellipsis in Spanish. (3rd February 2014) - Biezma, María
Abstract In this paper I use the case of Spanish to argue that language regularities may give rise to multiple strategies for marking focus. In addition to the well‐known observation that focus can be marked by word order and intonation, I present experimental results regarding ellipsis that show that overt full DPs in subject position in Spanish are marked as focused. This strategy is linked to a language regularity, namely the availability of silent (pro) subjects. In Spanish, there is a preference for pro subjects. Overt full DPs in subject position are marked, and the presence of overt full DPs is used to indicate focus on the subject (the pro‐drop hypothesis). I will provide a novel syntactic analysis of the ellipsis structures, discuss discourse licensing conditions and present two experiments that investigate preferences in ellipsis resolution and argue in favor of the pro‐drop hypothesis. Experiment 1 compares structural preferences for ellipsis resolution across bare argument ellipsis and replacives, investigating the role of syntax and the information‐structure status of the subject. Experiment 2 compares the resolution of ellipsis with antecedents with overt DP subjects versus pro subjects. The paper also establishes links with the processing of ellipsis in other languages.